Evaluating ecosystem impacts of biogas pathways using life cycle assessment and ecosystem service models - Kalu, Amarachi (International Journal of Sustainable Energy and Environmental Research, 2025)
The regional energy transition from fossil fuels to alternatives with lesser environmental impact has become significant in recent years. The UN and the Sustainable Development Goals (SDGs) emphasize the importance of cleaner, safer, and more modern energy production to support environmental and climate protection. Renewable energy-based agricultural feedstock is considered a better substitute; however, its increasing share among alternative technologies powered by biomass sources still requires comprehensive environmental impact assessments. This study employs Life Cycle Assessment (LCA) modeling to evaluate the environmental impacts of biogas pathways, focusing on maize silage production for biogas in Alberta, Canada. Using openLCA software and Eco-invent data, the analysis covers the entire supply chain from upstream to downstream, assessing emissions, land use, and climate change impacts. The methodology involved consulting literature reviews, utilizing databases such as Eco-Indicator 99, ReCiPe, and the Tool for the Reduction and Assessment of Chemical and Other Environmental Impacts (TRACI). Key findings indicate that nitrogen fertilizer use (above 120 kg/ha in the maize farm) significantly contributes to eutrophication. Additionally, drying maize silage with natural gas poses a high climate change potential. These insights suggest that while biogas from maize silage is not entirely environmentally benign, improvements are achievable through optimized practices.